Factors Influencing Decision Making for Carotid Endarterectomy versus Stenting in the Very Elderly - Heo, Sung Hyuk; Bushnell, Cheryl D. (Frontiers in Neurology, 2017)
Abstract As the population ages worldwide, the number of elderly patients with carotid stenosis is also increasing. There have been many large clinical trials comparing carotid endarterectomy versus stenting, but the inclusion criteria (i.e. symptomatic or asymptomatic), stenting methods (i.e. protection device), and primary endpoint (i.e. the definition of myocardial infarction and follow-up period) were different between trials. Therefore, the interpretation of those results is difficult and requires attention. When it comes to age, the patients older than 80 years were excluded or stratified to a high risk group in previous landmark trials. However, a recent guideline recommended that endarterectomy may be associated with lower stroke risk compared with carotid artery stenting in patients older than 70 years with symptomatic carotid disease. The annual risk of stroke in individuals with asymptomatic carotid stenosis is about 1-3%, but the risk is about 4-12% with symptomatic stenosis without carotid intervention. Although the outcome of carotid endarterectomy is better than that of carotid stenting in patients older than 70 years, the perioperative risk is higher in older patients. Therefore, it is important to classify high risk patients and consider underlying disability and life expectancy of very elderly patients before deciding whether to undergo a carotid intervention. In addition, we should also consider that the stroke rate with intensive medical treatment is unknown and is currently being investigated in randomized controlled trials. Intensive medical treatment includes high intensity statins, diabetes and blood pressure control, and aggressive antiplatelet treatment. The aim of this review is to report the factors that may be responsible for the variability in the treatment of carotid stenosis, particularly in the elderly population. This will allow the readers to integrate the current available evidence to individualize the treatment of carotid stenosis in this challenging population.